2017
DOI: 10.1007/s10653-016-9903-4
|View full text |Cite
|
Sign up to set email alerts
|

Healing and edible clays: a review of basic concepts, benefits and risks

Abstract: The use of clay by humans for medicinal and wellness purposes is most probably as old as mankind. Within minerals, due to its ubiquitous occurrence in nature and easy availability, clay was the first to be used and is still used worldwide. Healing clays have been traditionally used by man for therapeutic, nutritional and skin care purposes, but they could impart some important health and skin care risks. For instance, clay particles could adsorb and make available for elimination or excretion any potential tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(34 citation statements)
references
References 127 publications
0
26
0
3
Order By: Relevance
“…Researchers should be able to count on a set of empirical instrumental tests to quantify these properties. For a clay paste or peloid to be suitable for pelotherapeutic use, it should have certain properties such as a low cooling rate, a high absorption capacity and cation exchange capacity (CEC), good adhesiveness, ease of handling and a low hardness offering a pleasant feeling when applied to the skin [1,[11][12][13]].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers should be able to count on a set of empirical instrumental tests to quantify these properties. For a clay paste or peloid to be suitable for pelotherapeutic use, it should have certain properties such as a low cooling rate, a high absorption capacity and cation exchange capacity (CEC), good adhesiveness, ease of handling and a low hardness offering a pleasant feeling when applied to the skin [1,[11][12][13]].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, much attention should be paid to the clay component of the bottom sediment. Geological studies of other types of peloids have revealed that clay mineralogy and provenance are of crucial importance for correct understanding of the mechanism of this sediment formation [36][37][38]. Educational importance of the studied peloids is limited, partly due tothe high complexity of the processes of their formation.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, “ancient” agents such as clay minerals with demonstrated medicinal applications have become of interest ( 11 ). Clay minerals have been employed for reported curative and protective purposes (antiseptic or anti-inflammatory agents) since early history ( 11 , 12 ). Aside from the topical application of medicinal clays, geophagy or geopharma ( 13 ), representing the deliberate ingestion of “earth” materials for medicinal purposes such as healing gastrointestinal disturbances and/or supplementation of minerals, has also been practiced ( 12 , 14 16 ).…”
Section: Introductionmentioning
confidence: 99%